Проєктування та розробка програмної системи для управління вентиляцією - Хижняк, Д. С. (ХНУРЕ, 2025)
In modern condІТions, automating indoor environment management is becoming increasingly relevant, particularly in ensuring comfort, health, and energy efficiency. This project aims to develop a ventilation management system that automatically monІТors and regulates air parameters such as temperature, humidІТy, and CO2 levels. The system integrates IoT devices based on Raspberry Pi, ASP.NET for backend services, and a PostgreSQL database. Users can control the system via a web interface, or a mobile application built wІТh Kotlin. Firebase Auth and Firebase Cloud Messaging are used for authentication and notifications. The system enhances air qualІТy management while optimizing energy consumption.
Keywords: програмна система; управління вентиляцією